Natural products for the treatment and management of diabetes mellitus in Zimbabwe-a review - Usai, Remigio; Majoni, Stephen; Rwere, Freeborn (Frontiers in Pharmacology, 2022)
Use of medicinal plants and herbs in the treatment and management of diseases, including diabetes and its complications remains an integral part of African tradition. Diabetes mellitus or diabetes is one of the common health conditions that affects approximately 536.6 million people worldwide, and contributes to high morbidity and mortality in adult populations. In Africa, nearly 24 million adults ( 1.7% of African population) are living with diabetes mellitus. Due to the rising cost of modern medicine, the majority of people living in many rural parts of Africa rely on herbal plant medicine for the treatment of diabetes. This review highlights a number of studies carried out to evaluate the antidiabetic properties of indigenous plants found in sub-Saharan Africa with the goal of treating diabetes. Further, we discuss the mechanism of action of various plant extracts in the treatment and management of diabetes mellitus. Together, this review article can open pathways leading to discovery of new plant derived medicines and regularization of use of crude plant remedies to treat diabetes by governments across Africa.